Forbidden line ratios from Si viii and S x coronal ions - Dwivedi B.N. (My University, 2025)
The off-limb spectra, recorded by the NRL Skylab spectrograph, have been used to infer electron densities from theoretical curves of Si viii and S x density-sensitive line ratios. The derived densities are found to be in agreement with those reported by Feldman et al. (1978). Computed line intensities using the Kopp and Orrall (1976) model have also been used to estimate densities in the quite Sun and coronal holes from these curves. © 1991 Kluwer Academic Publishers.